Future practice : conversations from the edge of architecture - Hyde, Rory. (Routledge, 2013)
"Here, finally, is a resource outlining fifteen new architectural practice types to help you adjust to a rapidly changing market place. Perhaps your practice would work best as a community enabler, a management thinker, or a social entrepreneur. Author Rory Hyde has found innovators from every part of the architecture field, from firm directors to students, so that their experiences will resonate with yours. These conversations allow you to hear the solutions they've found in their own words, unfiltered, straight from the source, so that you can decide how they suit you. Future Practice includes interviews with Wouter Vanstiphout, architectural historian, Marcus Westbury, director of Renew Newcastle, Bruce Mau, graphic designer, Bjarke Ingels, director of BIG, Dan Hill, senior consultant at the Urban Infomatics division of ARUP, Steve Ashton, partner of Ashton Raggatt MacDougall and many more"--